Large Switchable Photoconduction within 2D Potential Well of a Layered Ferroelectric Heterostructure. Issue 37 (29th July 2020) - Yang, Yuben; Mao, Huican; Wang, Jing; Zhang, Qinghua; Jin, Lei; Wang, Chuanshou; Zhang, Yuelin; Su, Nan; Meng, Fanqi; Yang, Ying; Xia, Ruqiao; Chen, Rongyan; et al.
Abstract: The coexistence of large conductivity and robust ferroelectricity is promising for high‐performance ferroelectric devices based on polarization‐controllable highly efficient carrier transport. Distinct from traditional perovskite ferroelectrics, Bi2 WO6 with a layered structure shows a great potential to preserve its ferroelectricity under substantial electron doping. Herein, by artificial design of photosensitive heterostructures with desired band alignment, three orders of magnitude enhancement of the short‐circuit photocurrent is achieved in Bi2 WO6 /SrTiO3 at room temperature. The microscopic mechanism of this large photocurrent originates from separated transport of electrons and holes in [WO4 ] −2 and [Bi2 O2 ] +2 layers respectively with a large in‐plane conductivity, which is understood by a combination of ab initio calculations and spectroscopic measurements. The layered electronic structure and appropriately designed band alignment in this layered ferroelectric heterostructure provide an opportunity to achieve high‐performance and nonvolatile switchable electronic devices. Abstract : Coexistence of a 2D potential well and robust ferroelectric polarization is achieved in layered‐perovskite Bi2 WO6, leading to a large and stable photocurrent density in an artificially designed photosensitive Bi2 WO6 /SrTiO3 heterostructure. Such a prototype device shows a great potential for applications in high‐efficiency photovoltaic cells and nonvolatile information processing with low power consumption.